PENGARUH LEVERAGE DAN KUALITAS KEUANGAN TERHADAP PROFITABILITAS BANK PEMBANGUNAN DAERAH DI INDONESIA - Yolanda Tanika; Isfenti Sadalia (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT The issue of this research is to know whether the effect of leverage and financial quality is positive and significant impact on the profitability of the Regional Development Bank in Indonesia. Data collection was performed by collecting secondary data from annual financial reports of 25 Regional Development Bank in Indonesia, which comprises the balance sheet and income statement of a bank period 2007-2012. The method used is descriptive quantitative analysis using Multiple Linear Regression Analysis Method, with a significance level (α) = 5% for the hypothesis. The results of hypothesis testing by performing the F-test showed that the simultaneous use of leverage and financial quality-Altman Z-Score has positive and significant impact on the profitability of Regional Bank Development in Indonesia and t-test indicates that the DAR, DER, TIE positive and significant,LDAR negative and significant,LDER negative and not significant effect on the profitability of the Regional Development Bank in Indonesia. Keywords : Profitability, Leverage, Financial Quality